Continuum-electron interferometry for enhancement of photoelectron circular dichroism and measurement of bound, free, and mixed contributions to chiral response - R. Esteban Goetz; Alexander Blech; Corbin Allison; Christiane P. Koch; Loren Greenman (Physical Review Research)
We develop photoelectron interferometry based on laser-assisted extreme ultraviolet ionization for flexible and robust control of photoelectron circular dichroism in randomly oriented chiral molecules. A comb of XUV photons ionizes a sample of chiral molecules in the presence of a time-delayed infrared or visible laser pulse promoting interferences between components of the XUV-ionized photoelectron wave packet. In striking contrast to multicolor phase control schemes relying on pulse shaping techniques, the magnitude of the resulting chiral signal is here controlled by the time delay between the XUV and laser pulses. Furthermore, we show that the relative polarization configurations of the XUV and IR fields allow for disentangling the contributions of bound and continuum states to the chiral response. Our proposal provides a simple, robust, and versatile tool for the control of photoelectron circular dichroism and experimentally feasible protocol for probing the individual contributions of bound and continuum states to the photoelectron circular dichroism in a time-resolved manner.